Academic Perspective on 100 Days of Leadership: Local Government Leadership under Pressure - Delvita Juniarsih; Fatma Oktarendah; Johannes Johannes; Fatimah AS (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
The role of governors in leading economic and social transitions in transforming regions of Indonesia is crucial to achieving sustainability and stable growth. This article explores the concepts of transformational leadership and adaptive leadership in the context of significant economic change, particularly in relation to reducing dependence on extractive sectors such as mining and fossil fuels. Drawing on existing literature, this article identifies the challenges faced by governors in leading their regions through the stages of start-up, turnaround, accelerated growth, realignment, and sustaining success. Through the application of Michael Watkins' STARS model and Heifetz's theory of adaptive leadership, this article offers a deeper understanding of how governors can manage the transition to a green economy and mitigate the social impacts of major change. In addition, this article also highlights the importance of collaboration between the public, private, and community sectors in creating policies that support long-term sustainability.